Return to me [videorecording (DVD)] - Duchovny, David; Driver, Minnie; O'Connor, Carroll
Bob's happy marriage is shattered when his wife, Elizabeth, suddenly dies in a tragic accident. At the time, Grace begins to rebuild her life after receiving a heart transplant. Through fate, their lives constantly intertwine.